2020
DOI: 10.1111/trf.16198
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization characteristics, blood graft composition, and outcome in diffuse large B‐cell lymphoma after autologous stem cell transplantation: Results from the prospective multicenter GOA study

Abstract: Background Diffuse large B‐cell lymphoma (DLBCL) is a common indication for autologous stem cell transplantation (auto‐SCT). Study Design and Methods This prospective noninterventional study aimed to evaluate the impact of mobilization characteristics and graft cellular content on hematologic recovery and outcome after auto‐SCT among 68 patients with DLBCL. Results Better mobilization capacity as manifested by blood CD34+ cell count >32 × 106/L and CD34+ cell yield of the first apheresis >2.75 × 106/kg correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
3
7
1
Order By: Relevance
“…The MATRix combination was used in our study for the majority of the patients before BBBD treatment, which in turn has been proven to result in high remission rates before auto-SCT in a recent retrospective study [ 32 ] and also in a successful strategy for disease control during very long follow-up [ 32 ]. In the present study, a great majority (82%) of patients achieved CR before auto-SCT, but in contrast to previous report regarding DLBCL patients [ 18 ], we did not find any correlations with pretransplant disease status and survival possibly due to small study population.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The MATRix combination was used in our study for the majority of the patients before BBBD treatment, which in turn has been proven to result in high remission rates before auto-SCT in a recent retrospective study [ 32 ] and also in a successful strategy for disease control during very long follow-up [ 32 ]. In the present study, a great majority (82%) of patients achieved CR before auto-SCT, but in contrast to previous report regarding DLBCL patients [ 18 ], we did not find any correlations with pretransplant disease status and survival possibly due to small study population.…”
Section: Discussioncontrasting
confidence: 99%
“…Until now, the optimal thresholds of autograft cellular composition to be infused for lymphoma patients have not been established even if the most important parameter of graft quality has suggested to be the graft CD34 + cell content [ 15 - 17 ]. In the most recent prospective study of DLBCL patients including also some PCNSL patients [ 18 ], a cut-off point > 2.65 × 10 6 /kg of CD34 + cells infused was associated with not only more rapid hematologic recovery but in line with previous retrospective observations [ 19 , 20 ] also with better overall survival (OS). Higher CD34 + CD133 + CD38 - cell content of the graft has been shown to hasten hematologic recovery after auto-SCT [ 21 ] and in DLBCL patients also to correlate with better 5-year OS [ 18 ].…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“… 10 Further, a recent study showed a better 5-year overall survival when the patients are transplanted with higher number of CD34+ cells (>2.65×10 6 /kg). 11 …”
Section: Introductionmentioning
confidence: 99%